2019
DOI: 10.1038/s41598-019-42645-5
|View full text |Cite
|
Sign up to set email alerts
|

3D visualisation of hepatitis B vaccine in the oral delivery vehicle SBA-15

Abstract: Developing a technology that enables oral vaccines to work efficiently remains a considerable effort since a number of difficulties must be addressed. The key objective being to ensure the safe passage through the harsh conditions within the gastrointestinal tract, promoting delivery that induces enhanced immune response. In the particular case of hepatitis B, the oral formulation in the nanostructured silica SBA-15 is a viable approach. As a result of its porous structure, low toxicity and structural stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
(31 reference statements)
0
14
0
2
Order By: Relevance
“…SAXS characterization of the pure antigens in PBS solution (pH = 7.4 and T = 25 C) showed that HBsAg is a globular particle with mean diameter of 30 AE 5 nm, hence larger than the silica mean pore diameter D = 10.4 AE 0.6 nm, confirmed by DLS and TEM images (Rasmussen et al, 2019a). Therefore, the HBsAg particles are in the macroporous region of SBA-15, and may also close the entrance of the mesopore and cluster in PBS.…”
Section: Resultsmentioning
confidence: 83%
“…SAXS characterization of the pure antigens in PBS solution (pH = 7.4 and T = 25 C) showed that HBsAg is a globular particle with mean diameter of 30 AE 5 nm, hence larger than the silica mean pore diameter D = 10.4 AE 0.6 nm, confirmed by DLS and TEM images (Rasmussen et al, 2019a). Therefore, the HBsAg particles are in the macroporous region of SBA-15, and may also close the entrance of the mesopore and cluster in PBS.…”
Section: Resultsmentioning
confidence: 83%
“…About seven days before the oral vaccination administration, the dry fraction of the vaccine was prepared, measuring the number of proteins suspended in PBS (pH 7.2). The dose used for the production of the oral vaccine was 200 µg per piglet, mixed with silica in the proportion 1:35 defined in previous studies [ 14 , 26 ]. Mycoplasma hyopneumoniae protein lysate was added to SBA-15, previously macerated and activated, and a drying step at 37 °C for 72 h was performed to obtain the dry fraction [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of these new techniques as standard instrument options helped to expand the imaging capabilities of the beamline, allowing for imaging with polarized neutrons [7][8][9], Bragg-edge mapping [10][11][12][13], high-resolution neutron imaging [14] and grating interferometry [15,16]. These methods were offered to the user community as tools to help address scientific problems over a broad range of topics, such as superconductivity [17], materials research [18,19], life sciences [20,21], cultural heritage and paleontology [22,23]. Industrial applications, including fuel cell [24,25] and battery research [26][27][28], have also been fostered by these increased capabilities, which further helped to increase and improve the scientific output of the facility and to attract new users.…”
Section: -2010mentioning
confidence: 99%